Quality of life at work: the experience of health professionals in a Basic Health Unit in Minas Gerais - Brazil - Ernandes Gonçalves Dias; Alexandre Rodrigues dos Santos; Erleiane Lucinária Santos Souza; Marlúcia Mendes Ladeia Araújo; Janine Cinara Silveira Alves (Universidad de Alicante, 2017)
Objective: Verify the perception of suffering in the work of health professionals in the Basic Health Unit Delson Pinheiro de Aguiar in Serranópolis Minas. Methods: This is an exploratory cross-sectional study of qualitative approach. Data were collected from March to April 2015, through a semi-structured interview applied to 12 health professionals. Results: It was observed that most professionals find pleasure in work accomplished due helping others, contribute to improving the population's quality of life, bring information and relief of pain and pleasure for what they do. The situations that cause dissatisfaction or suffering at work are lack of recognition for the efforts made in implementing the work, indifference in interpersonal relationships between professionals and lack of friendship. Conclusion: In this way it is up for service managers intervene in the work process yielding to professionals best working conditions.